Reconstruction of the gravitational wave signal h(t) during the Virgo science runs and independent validation with a photon calibrator - Accadia, T.; Acernese, F.; Agathos, M.; Allocca, A.; Astone, P.; Ballardin, G.; Barone, F.; Barsuglia, M.; Basti, A.; Bauer, Th S.; Bejger, M.; Beker, M. G.; et al. (Iop Publishing Ltd, 2014)
The Virgo detector is a kilometer-scale interferometer for gravitational wave detection located near Pisa (Italy). About 13 months of data were accumulated during four science runs (VSR1, VSR2, VSR3 and VSR4) between May 2007 and September 2011, with increasing sensitivity. In this paper, the method used to reconstruct, in the range 10 Hz-10 kHz, the gravitational wave strain time series h(t) from the detector signals is described. The standard consistency checks of the reconstruction are discussed and used to estimate the systematic uncertainties of the h(t) signal as a function of frequency. Finally, an independent setup, the photon calibrator, is described and used to validate the reconstructed h(t) signal and the associated uncertainties. The systematic uncertainties of the h(t) time series are estimated to be 8% in amplitude. The uncertainty of the phase of h(t) is 50 mrad at 10 Hz with a frequency dependence following a delay of 8 mu s at high frequency. A bias lower than 4 mu s and depending on the sky direction of the GW is also present.
Keywords: Virgo; reconstruction; calibration; photon calibrator; gravitational wave; interferometer; h(t)